Pengaruh Environment dan Kepuasan Pelanggan pada Implementasi ISO 14000 di Perusahaan - Nabila Anedya Finatasya; Lita Aliyyusia; Latifah Ayu Tiarani; Roy Ade Melandry; Aulia Rahmah Anwar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Previous research has extensively observed how International Environmental Standards, commonly known as ISO 14000. However, research on the influence between X1, X2, and Y at PT. Futaba Industrial Indonesia has not been conducted before. Therefore, this study aims to analyze the influence of the work environment and customer satisfaction on the implementation of the ISO 14000 environmental management system. Using a quantitative approach, data were collected through questionnaires distributed to 52 respondents, consisting of employees at various levels of positions using the Simple Random Sampling technique. The research results show that the work environment variable has a significant impact on the implementation of ISO 14000. In addition, customer satisfaction also becomes an important factor in supporting the success of this system. This research emphasizes the importance of good workplace environmental management and improving customer satisfaction to ensure optimal environmental sustainability through the implementation of the international ISO 14000 standards.